Adenomyoepithelioma of the Breast: A Case Series - Wijegunarathna, K.V.C; Damayanthi, T; Wijesinghe, H.D; Dissanayaka, K.; Constantine, S.R (Annals of Pathology and Laboratory Medicine, 2025)
Adenomyoepithelioma (AME) is a rare biphasic breast tumor composed of epithelial and myoepithelial components. The majority of them are benign, and some can undergo malignant transformation, posing significant diagnostic and therapeutic challenges. We report three cases in postmenopausal women (ages 63-72) who presented with palpable breast masses, all radiologically categorized as BI-RADS 4B and confirmed by histopathology to have a classic AME pattern. Case 1 demonstrated malignant transformation into triple-negative invasive breast carcinoma and was treated with wide excision and chemotherapy, while Cases 2 and 3 were benign AMEs exhibiting sebaceous differentiation and were managed with mastectomy and local excision, respectively; all patients remained disease-free at 1-3 years of follow-up. This series underscores that careful morphological assessment and immunohistochemical staining for myoepithelial markers are crucial to distinguish AME from differential diagnoses like fibroadenoma or papilloma. Although most classic AMEs follow a benign course and are cured by complete excision, malignant variants, characterized by infiltrative growth, high mitotic rate, and atypia, lack a consensus management strategy and are typically treated with excision with or without adjuvant therapy.